EPILEPSY AND NON-EPILEPTIC PAROXYSMS AT CHILDREN OF THE MOGILEV AREA (on materials of work of children's neurologic branch of establishment of public health services «Mogilev regional children's hospital» during 2008-2012) - S. N. Prusakov; I. L. Malashko; T. S. Kaskova; M. G. Orlova (Эпилепсия и пароксизмальные состояния, 2016)
The purposes of researches were: studying concrete nosological forms of an epilepsy and no-epilepsy paroxysmes at children; the analysis of therapeutic efficiency of the basic groups against epileptic preparations. Materials and Methods. results of the analysis and an expert estimation of 1314 medical records are presented. The statistical analysis of the social status, perinatal and the genetic anamnesis, EEG-data and computer tomographic. Results of researches and approaches to appointment antiepilepsys preparations are presented at various forms of an epilepsy and others paroxysmes at children.